Transition program for adolescents with congenital heart disease in transition to adulthood: protocol for a mixed-method process evaluation study (the STEPSTONES project). Issue 8 (2nd August 2019) - Saarijärvi, Markus; Wallin, Lars; Moons, Philip; Gyllensten, Hanna; Bratt, Ewa-Lena
Abstract : Introduction: Today, the majority of young persons living with chronic conditions in high-income countries survive into adulthood and will need life-long medical follow-up. Therefore, transition programmes have been developed to facilitate transfer to adult care, and to support self-management and independence during adulthood. The Swedish Transition Effects Project Supporting Teenagers with chrONic mEdical conditionS (STEPSTONES) project aims to evaluate the effectiveness of a person-centred transition programme for empowering adolescents with congenital heart disease in transition to adulthood. To understand how the transition programme causes change and how outcomes are created, process evaluation is imperative to assess implementation, context and mechanisms of impact. This protocol aims to describe the process evaluation of the STEPSTONES transition programme. Methods and design: Medical Research Council guidance for process evaluation of complex interventions will be the guiding framework for this mixed-method study. The combination of qualitative and quantitative data will capture different aspects of programme delivery. The sample will consist of participants in the STEPSTONES randomised controlled trial (RCT), persons implementing the programme and healthcare professionals. Quantitative data will consist of protocols and routine monitoring documents from the RCT, data collected from patient registries and sociodemographic data to assess the implementation of the intervention. This data will be analysed with quantitative content analysis, along with descriptive and inferential statistics. Qualitative data will consist of participatory observations, logbooks and interviews with persons implementing the programme, participants and healthcare professionals. Analyses will be performed using qualitative content analysis to investigate mechanism of impact, context and delivery. Quantitative and qualitative data will be integrated in the final stage by using a triangulation protocol according to mixed-method guidelines. Ethics and dissemination: The study is approved by the Regional Ethical Review Board in Gothenburg, Sweden. Results will be presented in open access, peer-reviewed journals and at international scientific conferences.